Strategi Untuk Membangaun Kemandirian Ekonomi Masyarakat Dikelurahan Pamulang Timur - Styo Budi Utomo; Dean; Syifa; Nurul (Jurnal Abdimas Tri Dharma Manajemen, 2024)
This research aims to formulate an effective strategy in building the economic independence of thecommunity in Pamulang Timur Village. Economic independence is an important aspect to improvecommunity welfare and reduce dependence on external assistance. The approach used in thisresearch is a participatory method, where the community is actively involved in the process ofidentifying local potential, problems faced, and formulating solutions. SWOT analysis was used toexplore the strengths, weaknesses, opportunities, and threats in Pamulang Timur Village. Theresults showed that Kelurahan Pamulang Timur has several economic potentials that can bedeveloped, such as the trade sector, small and medium enterprises (SMEs), and urban agriculture.